Pedagogical Content Knowledge and Classroom Teaching of Mathematics Teachers at the Secondary Level - Mohalik, Ramakanta (JOURNAL OF INDIAN EDUCATION, 2013)
The present study was conducted to compare the pedagogical content knowledge and classroom teaching of mathematics teachers in relation to sex, qualification and experience and to find out the relationship between the pedagogical content knowledge and classroom teaching. The investigator adopted descriptive method. The tools consist of self-developed test on pedagogical content knowledge of mathematics and observation schedule for assessing classroom teaching of mathematics teachers. The study found that (i) There is no significant difference in pedagogical content knowledge and classroom teaching of male and female mathematics teachers. (ii) There is a significant difference in pedagogical content knowledge and classroom teaching of mathematics teachers in relation to qualification and experience. The teachers having higher qualification and teaching experience found having better pedagogical content knowledge and classroom teaching. (iii) The pedagogical content knowledge and classroom teaching of mathematics teachers is positively related both with respect to total sample and sub groups. Implication of the study is that teacher education institutes may think of enriching the Teacher Education curriculum incorporating adequate specific content that will help trainees to develop pedagogical content knowledge and educational authority may consider pedagogical content knowledge as criteria for the recruitment of teachers.